THE IMPACT OF SOCIAL TRUST AND SOCIAL INVESTMENT ON SOCIAL CAPITAL AND THE PERFORMANCE OF FARMER ORGANIZATIONS - Alsaba S. Igobula; Muhammad Yunus (UNIVERSITAS PGRI MADIUN, 2025)
This study examines the impact of social trust and social investment on social capital and the performance of farmer organizations in Indonesia, focusing on Gapoktan Torong Makmur in Batu City, East Java. Social trust and social investment are key dimensions of social capital that significantly influence the functioning and effectiveness of rural organizations. Employing a quantitative research design, the study collected primary data using structured questionnaires from 104 members of the organization. Data analysis was conducted using Partial Least Squares (PLS) for Structural Equation Modeling (SEM). Findings reveal that higher levels of social trust and increased social investment positively correlate with stronger social capital, which enhances cooperation, resource-sharing, and overall organizational performance. These results highlight the importance of fostering trust and social investment for the success and sustainability of farmer organizations, offering practical implications for rural development strategies in Indonesia. Key words: Social trust; social investment; social capital; farmer organizations; organizational performance